2005
DOI: 10.1111/j.1398-9995.2005.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

The autologous serum skin test in the follow‐up of patients with chronic urticaria

Abstract: The co-existence of autoimmune thyroiditis with chronic urticaria seems to induce a significant difference in the persistence of a positive ASST. Consistent with previous reports, a positive ASST correlates with disease exacerbation in chronic urticaria patients without thyroiditis. In patients with thyroiditis and urticaria, positive ASST persists even after the urticaria has disappeared, thus questioning whether a positive ASST to be a surrogate marker of the functional role of anti-FcepsilonRI and anti-IgE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
45
4
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 15 publications
(24 reference statements)
11
45
4
2
Order By: Relevance
“…Aversano et al [30] hypothesized that inflammatory status inflicted by TSH lead to flares of urticaria and also production of antithyroid antibodies. Unlike some investigators [19][20][21], we did not find a significant correlation between elevated TPO and positive ASST or CD63 expression. The finding in the present study is comparable with the study of Nettis et al, who did not detect a statistically significant difference between thyroid antibodies in either ASST positive or negative groups [31].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Aversano et al [30] hypothesized that inflammatory status inflicted by TSH lead to flares of urticaria and also production of antithyroid antibodies. Unlike some investigators [19][20][21], we did not find a significant correlation between elevated TPO and positive ASST or CD63 expression. The finding in the present study is comparable with the study of Nettis et al, who did not detect a statistically significant difference between thyroid antibodies in either ASST positive or negative groups [31].…”
Section: Discussioncontrasting
confidence: 99%
“…investigated 182 CU patients and found that thyroid antibodies were more common in patients with a positive ASST [19]. The same results were obtained by other authors [20,21].…”
Section: Introductionsupporting
confidence: 80%
“…This association has been verified by other groups [33][34][35]. Patients with chronic urticaria and evidence of autoimmune thyroid disease are more likely to have a positive basophil histamine-release assay [36] and a positive ASST [37,38]. A potential link with positive rheumatoid factor has been suggested [39].…”
Section: Associations Of Autoimmune Urticariamentioning
confidence: 61%
“…ile Fusari ve ark. ise yaptıkları çalışmalarda otolog serum testinin remisyonda da pozitifliğinin devam ettiğini bulmuşlardır (12,13). Diğer çalışmalarda tedaviye yanıt ve hastalık seyri ile ilişkisi bulunamamış olması da OST'nin güvenilirliğini şüpheye düşüren kanıtlar arasında yer almaktadır (14).…”
Section: Patogenez Teorileri -Otoimmün Teori;unclassified